Predicting Malaysian teachers' intention to apply for promotion - Adam Assim, Mohd Ibrani Shahrimin; Janis, Salina; Ahmad, Aminah (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
This study examined the predictors of behavior intention in career advancement, specifically the intention of applying for the ‘Excellent Teacher’ promotion award among teachers. Gender and self-efficacy of applicants are found to be related to intention to apply for promotion. Using the Theory of Planned Behavior (TPB) by Ajzen (1991) we examined the relationship between the predictor variables and intention to apply for promotion, with further exploration by including self-efficacy in applying for promotion and belief towards performance appraisal system for promotion. A total of 500 teachers consisting of male (226) and female (274) teachers who are qualified to apply for promotion participated in this study. This study also aimed to determine whether gender moderates the relationship between the predictor variables and intention to apply for promotion. Expectation of others towards qualifying candidates’ applying for promotion (EOQCAP) and belief towards a performance appraisal system (BPASPA) were significantly related to intention to apply for promotion. Attitude towards applying for promotion (AAP) and self-efficacy in applying for promotion (SEAP) were not significantly related. Using structural equation modeling, this study compared results between gender and concluded that not all relationships were moderated by gender. This study further explored the use of TPB by including CDSME and BTP to understand teacher intention to apply for promotion. We concluded that subjective norms and gender play vital roles in predicting teachers’ intention to apply for promotion.